2022
DOI: 10.3390/ani12192626
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Proline Supplementation on Goat Spermatozoa Quality during Cryopreservation

Abstract: Sperm cryopreservation contributes to the extensive utilization of artificial insemination (AI) in the daily livestock industry. However, due to the presence of few sperm with good biological function in post-thaw goat sperm, its use has been limited for AI purposes. Hence, its improvement has been the focus of many research studies. This study aimed to investigate the effects of proline supplementation of the freezing medium on goat sperm. The goat semen was cryopreserved with freezing medium supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…The recovery of cells cryopreserved in the freezing solution containing d -proline at 48 h after thawing was 87%, which was higher than that of cells cryopreserved in CELLBANKER 1 plus. The cryoprotective effect of l -proline has been reported in previous studies. ,, The present results showed that d -proline had a superior effect on cryopreservation of 2D-cultured cells.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The recovery of cells cryopreserved in the freezing solution containing d -proline at 48 h after thawing was 87%, which was higher than that of cells cryopreserved in CELLBANKER 1 plus. The cryoprotective effect of l -proline has been reported in previous studies. ,, The present results showed that d -proline had a superior effect on cryopreservation of 2D-cultured cells.…”
Section: Resultssupporting
confidence: 83%
“…28,29 L-proline and trehalose are natural cryoprotectants that accumulate in organisms as a defense mechanism against freezing in low temperature. 14,15,30 L-proline has been studied as a cryoprotectant for various biological samples, including red blood cells, 3 spermatozoa, 22,31,32 oocytes, 33 and stem cells. 34 Recently, the mechanisms by which L-proline aids in cellular cryopreservation have been postulated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We expected to see positive direct effects of antioxidants on motility but did not. Thus, removing antioxidants with lower loadings like melatonin and NGF may be advantageous, with the possibility of substituting more powerful antioxidants like proline [ 31 ] and humanin [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to know that dehydration will occur if there is higher osmotic pressure outside the cell. Some dehydration is beneficial for cryopreservation, as it reduces the formation of penetrating CPAs reproductive cells or even embryos of different species: avian sperm, 13 Nile tilapia sperm, 28 eel sperm, 29 Glossogobius giuris spermatozoa, 30 Mytilus embryos, 31 human oocytes, 32,33 human embryonic stem cells, 34 ovarian carcinoma cell lines, 35 and neuron-like cells 36 sulfoxides and amides DMSO, acetamide, dimethylformamide, or dimethylacetamide penetrating CPAs synthesized from dimethyl sulfide sperm cryopreservation methods, 39−53 Trichogaster fasciata embryos, 40,54 and human ovarian carcinoma cell lines (SKOV-3, OVCAR-8) 35 DMSO: limit ice nucleation and promote viability after thawing 37,38 amino acids and amines proline, glutamine, betaine, L-carnitine, or tricine neutral amino acids (β-alanine, γ-aminobutyric acid (GABA), and ε-aminocaproic acid (ε-Ahx)) proline: great osmoregulatory capacity, as well as a strong capacity to prevent water crystallization 55 proline: sperm samples, oocytes or in human endothelial cells 58 (sRBCs); 56 GLC-82, LTEP-a-2, 3T3 and smooth muscle cells; 55 Jurkat cells; 26 and human spermatozoa 59 proline + trealose: preservation of cell morphology 56 glutamine: spermatozoa, including humans, 60 boar, 61 ram 62 and rooster, 63 and epididymal sperm in Egyptian spiny mice 20 glutamine: improves motility and protects membrane integrity against damage caused by the freeze−thaw process 20 neutral amino acid-based (β-alanine, γ-aminobutyric acid (GABA), and ε-aminocaproic acid (ε-Ahx)) CPA solutions: cryopreserve GLC-82 cells and SMCs 64 betaine: hydrophilic molecule that has a high capacity for hydration through the ionic solvation effect with its charged groups (inhibitor of ice formation) intracellular ice. However, if the dehydration is very high, then irreversible damage to the cell can occur because of cryopreservation.…”
Section: Introductionmentioning
confidence: 99%